Teaching Improvisation through Processes. Applications in Music Education and Implications for General Education - Biasutti, Michele (Frontiers in Psychology, 2017)
Improvisation is an articulated multidimensional activity based on an extemporaneous creative performance. Practicing improvisation, participants expand sophisticated skills such as sensory and perceptual encoding, memory storage and recall, motor control, and performance monitoring. Improvisation abilities have been developed following several methodologies mainly with a product-oriented perspective. A model framed under the socio-cultural theory of learning for designing didactic activities on processes instead of outcomes is presented in the current paper. The challenge is to overcome the mere instructional dimension of some practices of teaching improvisation by designing activities that stimulate self-regulated learning strategies in the students. In the article – the present thesis – is declined in three ways, concerning the following three possible areas of application: 1) high-level musical learning, 2) musical pedagogy with children, 3) general pedagogy. The applications in the music field focusing mainly on an expert’s use of improvisation are discussed. The last section considers how these ideas should transcend music studies, presenting the benefits and the implications of improvisation activities for general learning. Moreover, the application of music education to the following cognitive processes are discussed: anticipation, use of repertoire, emotive communication, feedback and flow. These characteristics could be used to outline a pedagogical method for teaching music improvisation based on the development of reflection, reasoning, and meta-cognition.